Performance analysis of the cooling tower at PT PLN IP PLTP Ulumbu - Karolus Risandi Jebarus; Sugeng , Margono (JTTM : Jurnal Terapan Teknik Mesin, 2025)
This research focuses on the analysis of one of the important components in the Ulumbu Geothermal Power Plant (PLTP), namely the cooling tower, which plays a vital role in reducing water temperature through evaporative heat transfer. The purpose of this study was to evaluate the performance of the cooling tower operated by PT PLN Indonesia Power Services. Data was collected for four consecutive weeks by recording key parameters such as inlet and outlet water temperatures, ambient air temperature, and wet and dry bulb temperatures. These parameters were used as the basis for calculating cooling efficiency and avaluating the overall system performance. The results showed that the cooling tower operated with relatively stable efficiency, with a temperature drop (ΔT) ranging from 7.1°C to 8.2°C and an efficiency level between 40.2% and 42.9%. Despite variations in ambient air temperature during the observation period, the system remained operating under acceptable conditions. Therefore, regular monitoring and maintenance are necessary to maintain the system's optimal function